Van Abbemuseum : het collectieboek - Debbaut, Jan; Verhulst, Monique (Eindhoven : Van Abbemuseum, 2002)
Abramovic, Marina & Ulay ; Ahtila, Eija-Liisa ; Alechinsky, Pierre ; Andre, Carl ; Anselmo, Giovanni ; Appel, Karel ; Arman ; Armando ; Art & Language ; Atelier van Lieshout ; Attersee, Christian Ludwig ; Bacon, Francis ; Baer, Jo ; van Bakel, Gerrit ; Baldessari, John ; Baljeu, Joost ; Balka, Miroslav ; Barry, Robert ; Baselitz, Georg ; Baumgarten, Lothar ; Bazaine, Jean ; Becher, Bernd & Hilla ; Beckmann, Max ; Beuys, Joseph ; Bissière, Roger ; Boezem, Marinus ; Boltanski, Christian ; Bonies, Bob ; Boonstra, Marjoleine ; Braque, Georges ; Broodthaers, Marcel ; Brouwn, Stanley ; Brusselmans, Jean ; Buren, Daniel ; Bustamante, Jean-Marc ; Byars, James Lee ; Cadere, Andre ; Campendonk, Heinrich ; Chabot, Hendrik ; Chagall, Marc ; Chaissac, Gaston ; Charlton, Alan ; Christo ; Coleman, James ; Constant ; de Cordier, Thierry ; Corneille ; Cragg, Tony (Anthony) ; Daniels, René ; Dekkers, Ad ; Delaunay, Robert ; Dibbets, Jan ; Dijkstra, Rineke ; Dine, Jim ; van Doesburg, Theo ; Dubuffet, Jean ; Dumas, Marlene ; van Elk, Ger ; Ernst, Max ; Fabro, Luciano ; Fernhout, Edgar ; Flanagan, Barry ; Riverhead (New York) ; Fontana, Lucio ; Francis, Sam ; Fulton, Hamish ; Genzken, Isa ; Gestel, Leo ; Gilbert & George ; Gnoli, Domenico ; Gordon, Douglas ; Graham, Dan ; Graham, Rodney ; Gris, Juan ; Haacke, Hans ; Finlay, Ian Hamilton ; Hamilton, Ann ; Hartung, Hans ; Hill, Gary ; van Hoek, Hans ; Horn, Rebecca ; Huebler, Douglas ; Huyghe, Pierre ; Iglesias, Cristina ; Immendorff, Jörg ; Indiana, Robert ; Jorn, Asger ; Judd, Donald ; Kandinsky, Wassily ; Kapoor, Anish ; Kawara, On ; Kelly, Ellsworth ; Kemps, Niek ; Kiefer, Anselm ; Kirkeby, Per ; Klein, Yves ; Klingelhöller, Harald ; Knoebel, Imi ; Koelewijn, Job ; Kokoschka, Oskar ; Körmeling, John ; Kosuth, Joseph ; etc.
boek